Perancangan Aplikasi Kolaborasi Dokumen Berbasis Web Dengan Menggunakan HTML 5 dan PHP - Budi Wasito (Jurnal Informatika dan Bisnis, 2013)
Computerized technology is currently supported Internet progressed rapidly. Besides the speed of the process, many of computerized support saving storage media. Supported with the progress in field of communication such as internet service, the process becomes faster and more increased, and especially saving time and cost. Along the development of time, people start demanding things for very practical. The purpose of this application is to makes it easy the process of creating or modifying a document together with real-time thereby accelerating job or our task.Applications Document Collaboration developed uses HTML5, supported by PHP programming language as a communicator between pages, and CSS3 which supports design. Database system uses MySQL.Data collection was conducted by literature studies, Workflow and processes on the system is described by use case diagrams and sequence diagrams. The results of this research is Applications Document Collaboration developed that allows web users to create and modify documents online. Registered users can also use additional features such as publish the articles that have been written online, and can upload files online. Web-Based Applications Document Collaboration can makes it easy and shorten the process of creating or modifying a document that we should do in group.